Scott thornbury's 30 language teaching methods - Scott Thornbury; Kerr, Philip; ed. (New York Cambridge University Press, 2017)
Scott Thornbury's very accessible 30 Teaching Methods, groups methods according to what they have in common, even if separated in time. At the same time, it rehabilitates some lost or forgotten methods, with a view to challenging current orthodoxies, especially with regard to such topics as translation, rote learning, authenticity, and communication. In doing this it aims to unpack, not just the history of methods, but the beliefs that underpin them and the benefits that still might possibly accrue from experimenting with them. Through its inclusion of interesting characters, intriguing anecdotes, and often bizarre techniques, the material is absorbing and engaging.
Keywords: Language